General equilibrium, overlapping generations models, and optimal growth theory - Bewley, Truman F. (Truman Fassett), 1941- (Harvard University Press, 2007)
This book presents an exposition of general equilibrium theory for advanced undergraduate and graduate-level students of economics. It contains discussions of economic efficiency, competitive equilibrium, the welfare theorems, the Kuhn-Tucker approach to general equilibrium, the Arrow-Debreu model, and rational expectations equilibrium and the permanent income hypothesis. It presents a unified approach to portions of macro- as well as microeconomic theory and contains problems sets for most chapters.